MIDWIVES’ SUPPORT DURING PUERPERIUM AMONG WOMEN WHO HAVE UNDERGONE INFERTILITY TREATMENT - Yuki Kanazawa; Komachi Ouki; Atsuko Kawano (Journal of Maternity Care and Reproductive Health, 2022)
Objective: This study aims to reveal the types of support that midwives provide to mothers during the postpartum period after infertility treatment.Methods: Sixteen midwives, who had experience dealing with mothers in the puerperium after infertility treatment, participated in semi-structured interviews.Results: To determine the roles of mothers, the following nine categories regarding midwives’ support for puerperal women after infertility treatment were identified: 1) midwives listen more carefully to puerperal women who have undergone infertility treatment than to those who have experienced natural childbirth, 2) midwives encourage adding milk when breast milk is insufficient for the baby’s growth, 3) midwives assist women who have undergone an emergency caesarean section overcome the feeling of regret and remain positive, 4) midwives recognize that there are many elderly women, 5) midwives’ level of support during the puerperium after natural pregnancy and after infertility treatment is identical, 6) midwives are involved in the step-by-step process of the mother becoming a parent, 7) midwives are involved in raising the child positively, 8) during the semi-monthly and monthly health check-ups, midwives encourage and instill confidence in mothers, and 9) midwives help mothers cope with anxiety regarding the lack of or poor weight gain among their children.Conclusion: Midwives play a significant role in reducing anxiety among puerperal women that have undergone infertility treatment by providing consistent emotional support to such women, even after discharge.